The Role of Digital Banking Industry Towards Consumer Behavior During The Covid 19 - Aniqoh, Nur Aini Fitriya Ardiani; Nihayah, Ana Zahrotun; Amalia, Farah (Fakultas Ekonomi dan Bisnis Islam UIN Walisongo, 2022)
Covid 19 has had an impact on various changes, especially with the revolution towards a digital base, one of which is the banking system. This study aims to analyze the role of the digital banking industry in consumer behavior during Covid 19. The general objective of this research is to assist the government in determining appropriate policies regarding the digital banking industry. Referring to the formulation of the problem, this research uses a qualitative descriptive approach. Descriptive method is a method that describes an objective event or certain events based on visible or proper facts which are then accompanied by efforts to make general conclusions based on these historical facts. The Covid 19 pandemic has had a significant impact on the Indonesian economy due to a policy implemented by the government which prohibits people from gathering in large numbers. This policy makes people get used to utilizing various financial technologies to carry out their lives. Therefore, banks must accelerate the use of digital banking services. The implementation of digital banking can accelerate public acceptance of digital transformation. The banking industry needs to take advantage of the conditions of the Covid-19 pandemic to accelerate digital investment and further increase efficiency. Basically, banking has been carrying out digital innovations for a long time, including in the development of mobile banking and a number of other applications and platforms. This research will provide policy benefits in strengthening government institutions, especially the banking industry to control the implementation of digital banking in Indonesia so that it has a positive impact on consumer behavior.